Instalação artística na educação infantil: as experiências estéticas das crianças de uma EMEI em Belo Horizonte. - Márcia Dárquia Nogueira da Silva (2021)
The general purpose of the thesis was to investigate and analyze how five-year-old children experience art from the proposition of an art installation in a process of intervention in the context of a Municipal School of Early Childhood Education - EMEI - in Belo Horizonte, MG. We also had as specific objectives: to describe and analyze the installation as an artistic process; to discuss and build, with the children, installations in the school space; to observe how the children live experiences in art from the proposition of art installations; to analyze what the children say about the process experienced in the production of an installation; to understand which signs emerge from the children's perspective about the installation that can subsidize the pedagogical practice in Early Childhood Education. In order to achieve the stated objectives, the children were invited to get closer to art processes through the proposition of an installation. We studied and dialogued with the children about installation concepts, introducing Artur Barrio and Ernesto Neto to them, artists who are dedicated to this form of expression. Theoretically, the research was anchored on authors who discuss the relationship between childhood and education (LUZ, 2008; KRAMER; ROCHA, 2011); childhood and art (LOPONTE, 2008; CUNHA, 2015 and 2017); art and education (BARBOSA, 2005 and 2012; MACEDO, 2010); art and experience (DEWEY, 2010); and body and experience (MERLEAU-PONTY, 2018). For further analytical study, the concepts of research with children (CRUZ, 2008 and 2010; CORSARO, 2005 and 2009), art installation (HUCHET, 2005; TESSLER, 2000); creative imagination (VYGOSTKY, 2009); and aesthetic experience (DEWEY, 2010) were also approached. Methodologically, we based our work on the qualitative approach of educational research with ethnographic procedures in order to ensure greater accuracy in the data construction, treatment and analysis, combining different elements such as immersion in the field, participant observation, notebook recordings, audio and video recordings, production of drawings and various records by the children, in addition to conducting individual, in pairs and in groups interviews. The combination of strategies and procedures for field research was based on the Mosaic Approach proposed by Alison Clark (2005). As a result, the research revealed, among other things, that the children’s aesthetic experiences in the context of an art installation occur in the relationship between body, space, time, materiality, experimentation, research, and creation; that an art installation enhances the constitutive elements of children's experiences; that the relationship established between art, childhood and contemporary metaphors contributes for such experiences to be elaborated, articulating knowledge, experimentation and production; that the construction of an art installation with children from Early Childhood Education can mobilize numerous perceptions and aesthetic experiences as long as it brings together the playful, installer and poetic being of the children.